Role of nursing in the care of the patient with respiratory failure - Hilda-Lucila, Chávez G.; Ureta-Rios, Lenny Y.; Ponce-Valencia, Alicia; Cabanillas-Chavez, María Teresa; Morales Garcia, Wilter C. (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Introduction: Respiratory failure is a pathological condition, it originates when the lungs are not able to eliminate the accumulation of carbon dioxide, impairing oxygenation in the blood, decreasing oxygen supply to tissues and even causing death. Objective: To describe the role of nursing in the care of patients with acute respiratory failure in the Pediatric Emergency Department of a hospital in Lima, in order to avoid prolonged hospital, stay and the complications that may arise from the process. Methodology: A qualitative study was carried out, with a single clinical case design, based on the Nursing Care Process (PAE) method, the instrument used was a Marjory Gordon functional pattern assessment guide, in a 4-year-old patient. The assessment was carried out in detail and then the nursing diagnoses according to NANDA were enunciated, then the care plans were prepared with the corresponding objectives and interventions and finally the evaluation was carried out. Results: 8 nursing diagnoses were identified, priority was given to the diagnosis: ineffective respiratory pattern r/c respiratory muscle fatigue e/p dyspnea, tachypnea, nasal flaring, the interventions performed were satisfactory, the patient's respiratory pattern improved, however, the results of the sepsis CP are still undefined due to the few hours of care and ntervention.